KNOWLEDGE, ATTITUDE AND PRACTICE ON BIRTH PREPAREDNESS AND COMPLICATION READINESS AMONG PREGNANT WOMEN ATTENDING ANTENATAL CARE AT CHIRO ZONAL HOSPITAL EASTERN ETHIOPIA - Bekele, Shiferaw; Alemayehu, Tadesse (Ethiopian Journal of Reproductive Health, 2018)
ABSTRACT BACKGROUND: Birth preparedness and complication readiness is a com prehensive strategy to improve the use of skilled providers at birth, and the key intervention to decrease maternal mortality. It is also a key component of globally accepted safe motherhood programs. OBJECTIVE: To assess the knowledge, attitude and practices about birth preparedness and complication readiness among pregnant women attending antenatal care at Chiro Zonal Hospital, East Ethiopia. METHODS: Hospital based cross sectional study was conducted on a sample of 418 pregnant women. Exit interview using a pretested structured questionnaire was used to collect data from pregnant women attending antenatal care at Chiro Zonal Hospital. The collected data was cleaned, coded and analyzed using SPSS version 20 statistical package. RESULT: Twenty percent had knowledge of one key danger signs during pregnancy, child birth and postpartum and 61.2% had favorable attitudes towards birth preparedness and complication readiness. Knowledge of at least one key danger signs during pregnancy, child birth and post partum, attitudes towards birth preparedness and practice of birth preparedness were associated with birth preparedness and complication readiness. CONCLUSION AND RECOMMENDATION: Both knowledge of obstetric danger signs and birth preparedness and complication readiness were low. Enhancing women’s awareness and improving the quality of labour wards would improve delivery service utilization. KEYWORDS: Birth preparedness, complication readiness, antenatal care, pregnant women (Ethiopian Journal of Reproductive Health 2018; 10; 3: 55-64)